The Importance of Use of Computer Technology in Ecological Livestock - Hasan Çelikyürek; Kadir Karakuş (Turkish Journal of Agriculture: Food Science and Technology)
Ecological livestock is a production method which allows all kinds of natural behaviors to be shown, fed with ecological feeds, in order to increase efficiency additives are not used, healthier products are offered to consumers, is sensitive to environmental awareness and animal rights. Especially in recent times, livestock sector has been in demand due to significantly increase of demand for ecological products. Main purpose of ecological agriculture is maintaining production optimization in the life chain between soil, plants, animals and humans healthfully. For this purpose, it is necessary that computer technology should be used at every stage of ecological animal husbandry. Although family-run businesses are in the forefront nowadays, computer technology is not utilized sufficiently. Consequently, information cannot be recorded regularly at every stage of breeding by them. Essential automation system is accompanied by record keeping system that is obligatory and necessary for ecological animal husbandry. Utilizing computer technologies will be crucial in terms of effective use of livestock organizations, creation of ecological animal production policies and strategies, and more active involvement in production planning.